Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T16:59:55+01:00
A) 2a+3-a+6+7a dla a= -2
8a+9=8*(-2)+9=-16+9=-7

b) 2z+t-3z+4t-1 dla z= 5 i t=0,1
-z+5t-1=-5+5*0,1-1= -6+0,5=-5,5

c) 13x-2y+7-9x+y-4+x-3 dla x=0,2,y= -1
5x-y= 5*0,2+1=1+1=2

d) n²+n-7+3n²-n-9-n+16 dla n=-1/2
4n²-n=4*(-½)² +½=4*¼ +½= 1½
2010-01-13T17:04:17+01:00
A) 2a+3-a+6+7a dla a= -2
2*(-2)+3-(-2)+6+7*(-2)= -4+3+2+6-14= -7

b) 2z+t-3z+4t-1 dla z= 5 i t=0,1
2*5+0,1-3*5+4*0,1-1= 10+0,1-15+0,4-1= -5,5

c) 13x-2y+7-9x+y-4+x-3 dla= x=0,2,y= -1
13*0,2-2*(-1)+7-9*0,2+(-1)-4+0,2-3= 2,6+2+7-1,8-1-4+0,2-3=2

d) n²+n-7+3n²-n-9-n+16 dla n=-1/2
-0,25-0,5-7+3*(-0,25)+0,5-9+0,5+16= -0,25-0,5-7-0,75+0,5-9+0,5+16=-0,5

2010-01-13T17:06:24+01:00
A) a) 2a+3-a+6+7a
2a+3-a+6+7a=8a+9=8×(-2)+9=-7

b)2z+t-3z+4t-1=-1z+5t-1=-1×5+5×0,1-1=-5+0,5-1=-5,5

c) 13x-2y+7-9x+y-4+x-3 dla= x=0,2,y= -1
13x-2y+7-9x+y-4+x-3 = 5x-y = 5×0,2-(-1)= 2

d) n²+n-7+3n²-n-9-n+16 dla n=-1/2
n²+n-7+3n²-n-9-n+16= 4n²-n = 4×(-1/2)²-(-1/2)=4×0,25+0.5=1.5